SOSIALISASI DAN PELATIHAN STRATEGI PEMASARAN DALAM MENINGKATKAN PPDB DI SEKOLAH MENENGAH KEJURUAN (SMK KRISTEN NUSANTARA KUDUS) - Bellachintya Reira Christata; Dina Tauhida; Adhie Prayogo; Salman Alfarisi; Gefina Nissa Belinda (Universitas Mataram, 2025)
Kudus Regency has shown significant progress in education, as reflected in its highest Human Development Index (HDI) achievement among the former Pati Residency region. Amid increasing competition among schools, particularly private vocational high schools (SMK), SMK Kristen Nusantara Kudus has experienced a decline in student enrollment due to suboptimal promotional strategies. This challenge demands a digital-based promotional approach, including the use of social media and segmented marketing strategies tailored to target audiences. Therefore, a community service program was initiated in the form of training on school marketing strategies to enhance the school's competitiveness and attractiveness during the student admission period (PPDB). The goal of this community service activity is to provide training and assistance to the school management in designing and implementing effective, digital-based school marketing strategies, aimed at improving visibility, attractiveness, and the number of new student enrollments. The method used in this program involved several stages: socialization, training, implementation, mentoring, and sustainability. The program was attended by all teachers and staff of the school. The community service activities at SMK Kristen Nusantara Kudus have successfully improved the understanding and skills of teachers and staff in planning and executing effective school marketing strategies for PPDB. The outcomes include a better understanding of digital-based marketing strategies, and improved school visibility and public image through social media content. This activity showed positive impacts, such as increased digital interaction and a 30% increase in enrollment from the previous academic year.